Cohort differences in the urban settlement intentions of rural migrants: A case study in Jiangsu Province, China. (October 2015) - Tang, Shuangshuang; Feng, Jianxi
Abstract: China has experienced a massive rural-urban migration process since the mid-1980s. During the period, a new generation of rural migrants has increasingly accounted for a large segment of the total floating population. The younger generation differs from its predecessors with respect to certain characteristics, exhibiting improved human capital, less farming experience and a stronger desire for urban settlement. This generation prefers to settle in urban areas rather than return to rural hometowns to farm. Although the topic of permanent migration and urban settlement is an issue confronting China and other countries, research focussing on cohort differences in urban settlement decisions is limited. The paper, which reports the results of a 2010 survey of rural migrants in Jiangsu Province, China, provides an in-depth comparison of the determinants of urban settlement for younger and older generations for different types of urban destinations. Survey respondents were divided into two cohorts based on birth year, and both geographic and socioeconomic factors were examined. Binary logit regression models found that disparities between the two generations were related to differences in the life-cycle stages of the two cohorts, attitudes and behaviours, and recent economic and social transitions in Jiangsu Province. Highlights: Significant differences in settlement intention between two generations are observed. Life-cycle differences and period effects are the two main reasons for the differences. The influences of socio-demographics and location factors of migrations vary with the scale of cities. Administrative level of destination cities also influences migrants' settlement intentions.